THE INFLUENCE OF CANNABIS ON THE DEVELOPMENT OF SCHIZOPHRENIA - A REVIEW - Artur Hawajski; Weronika Mielnicka; Jan Nowak; Stella Mieruszyńska; Julia Sławińska; Olga Szeidl; Maja Kołodziejska; Marcin Lewandowski; Anna Cupiał; Jagoda Mikołajczyk (International Journal of Innovative Technologies in Social Science, 2026)
Background: Schizophrenia is a complex mental disorder influenced by both genetic and environmental factors. Cannabis use, particularly products with high tetrahydrocannabinol (THC) content, has been identified as a potential environmental risk factor for psychosis. Aim: This review aims to summarize current knowledge on the epidemiology, etiopathogenesis, and risk factors of schizophrenia, with a particular focus on the impact of marijuana use on the development of psychotic symptoms. Methods: A narrative synthesis of epidemiological, genetic, neurobiological, and clinical studies was conducted, including analyses of cannabis use, THC potency, and age of first exposure. Results: Evidence indicates strong familial aggregation of schizophrenia and sex-related differences in the age of onset. Genetic studies highlight polygenic susceptibility, dopaminergic and glutamatergic dysregulation, and the impact of prenatal and early-life exposures. High-THC cannabis use, especially during adolescence, is associated with increased risk of psychotic symptoms, earlier onset, and more severe disease progression. Rising THC concentrations and increasing cannabis consumption pose significant public health challenges. Conclusions: Understanding the dose-dependent effects of cannabis on schizophrenia is critical for prevention strategies and public health policy, particularly in the context of increasing legalization and product potency.